Evaluasi Penerapan E-Government dalam Pembuatan E-KTP di Kantor Dinas Kependudukan dan Pecatatan Sipil Kabupaten Pinrang - Warahma, Mawadda; Muhiddin, Amir; Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This study aims to describe and analyze the implementation of e-Government in the issuance of e-KTPs at the Population and Civil Registration Office of Pinrang Regency. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. The theory used in this study is the evaluation theory developed by William Dunn (2003:610), which examines the impact on effectiveness, efficiency, quality, performance, and productivity. The results show that e-Government provides benefits to the community in the issuance of e-KTPs at the Dukcapil Office. The responsibility of the Population and Civil Registration Office of Pinrang Regency is like that of a beautiful operator to the community. In general, the implementation of e-Government has had a positive impact on the community, although improvements are needed from all parties to create a more equitable and sustainable partnership.